Integrasi Al-Qur’an dan Al-Hadits Dalam Pengembangan Pendidikan Islam di Madrasah Tsanawiyah Thoiyyib Hasyim Jorongan Leces Probolinggo: Tantangan dan Peluang Dalam Menyongsong Era Digital dan Globalisasi - M. Romli; Ainur Rofiq Sofa (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2025)
Islamic education at Madrasah Tsanawiyah Thoyyib Hasyim Jorongan Leces Probolinggo is committed to integrating and applying the teachings of the Qur'an and Hadith in all aspects of education, with the aim of shaping students who are not only intellectually competent but also possess noble character as a fundamental aspect of their personality. This research aims to explore the forms, processes, opportunities, challenges, and implications of integrating the Qur'an and Hadith in the development of Islamic education at this institution. The results of the study show that Madrasah Tsanawiyah Thoyyib Hasyim Jorongan Leces Probolinggo integrates Islamic values into various subjects, such as mathematics, science, and religious studies, through an interdisciplinary approach. The strengthening of students' character is carried out through routine activities based on the teachings of the Qur'an and Hadith, such as congregational prayers and reading the Qur'an. Despite the challenges related to teachers' limited understanding in integrating religious values with general subjects, there are significant opportunities to develop Islamic-based education. The implications of this integration include the formation of students with piety, noble character, and responsibility. Strategies that need to be implemented to strengthen this integration in the future include the development of a more flexible curriculum, continuous teacher training, and the utilization of technology in learning. Therefore, Madrasah Tsanawiyah Thoyyib Hasyim Jorongan Leces Probolinggo has successfully created a synergy between academic education and religious education, providing students with knowledge for both this world and the hereafter